The Effect of Animal Bone Fat on Body Performance and Carcass Characteristics in Broilers - Calislar, S.; Aydin, R. (International Journal of Poultry Science, 2006)
The objective of this study was to determine the effects of animal bone fat on the body performance, feed efficiency, body composition and blood glucose, lipoproteins and total protein in broilers. In this study, 8-day old Ross PM3 male broiler chicks were randomly distributed into five groups with three replicates of 24 birds each (72 chicks per group) and were fed diets containing 0 (Group A, control), 2% (Group B), 4% (Group C), 6% (Group D) or 8% (Group E) for 6 weeks. Diets contained 23% CP and 3100 kcal of ME were given between day 8 and 21 and then diets containing 21% CP and 3200 kcal of ME were given on the days between 22 and 49. Body performance, feed intake and feed conversion rate were evaluated. The water content, crude protein, fat, ash, and abdominal fat were analyzed. Blood samples (3 per group) were collected on the 14th day of the study for analysis of glucose, lipoproteins and total proteins. Feeding animal bone fat increased body weight gain, feed efficiency, cold carcass weight and abdominal fat weight. As the level of animal bone fat was increased in the diet, relative level of carcass water decreased and carcass fat level increased significantly. Abdominal adipose tissue level (%) was significantly higher in the Group E compared to the other groups. There were no effects of feeding animal fat on the level of blood glucose, but the levels of plasma total protein and total lipoprotein increased significantly. This study indicated that animal bone fat significantly influenced the live weight gain, feed efficiency, cold carcass weight and abdominal fat level. This study also showed that dietary animal fat significantly affected body composition, plasma proteins and lipoproteins, but not the glucose levels.